Energy Aware Consolidation for Cloud Computing - Srikantaiah, Shekhar; Kansal, Aman; Zhao, Feng (USENIX HotPower'08: Workshop on Power Aware Computing and Systems at OSDI, 2008)
Consolidation of applications in cloud computing environments presents a significant opportunity for energy optimization. As a first step toward enabling energy efficient consolidation, we study the inter-relationships between energy consumption, resource utilization, and performance of consolidated workloads. The study reveals the energy performance trade-offs for consolidation and shows that optimal operating points exist. We model the consolidation problem as a modified bin packing problem and illustrate it with an example. Finally, we outline the challenges in finding effective solutions to the consolidation problem.